E-Commerce: Challenges and Opportunities for Women Entrepreneurs - Gupta, Neeti (AMC Indian Journal of Entrepreneurship, 2019)
Women play significant roles in our society but when it comes to business, traditional businesses in India are male dominated. Moreover, while taking care of home and hearth, fulfilling the dream of owning a business is a challenge for women entrepreneurs. E-commerce, which suits almost all types of businesses is becoming the biggest platform to fulfill their dreams. Information technology is giving women freedom to work from the comfort of their homes. The growth of e-commerce has helped women entrepreneurs to generate new ideas and work by setting their own work schedule. Therefore, to reap the benefits of new technology, it is important to analyze available opportunities and constraints in e-commerce for women entrepreneurs. This paper discusses various challenges faced by women who want to use online platforms to start, grow, and sustain their business. It also describes available opportunities to encourage women to use an online platform for writing their success story.